PENGARUH MODEL PEMBELAJARAN PICTURE AND PICTURE BERBANTUAN WORDWALL TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD - Sutanto, Sutanto; Rosmaiyadi, Rosmaiyadi; Hendriana, Evinna Cinda (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to determine whether there is an effect of the Picture and Picture learning model assisted by Wordwall on the science (IPAS) learning outcomes of fourth-grade students at SDN 89 Singkawang. This research employed a quasi-experimental design with a posttest-only control design. The population consisted of all fourth-grade students at SDN 89 Singkawang, and the sampling technique used was total sampling. Data were collected through questionnaires and tests. The data analysis techniques included normality test, homogeneity test, t-test, effect size calculation, and response questionnaire analysis. The results of the study show that: (1) there is a significant difference in IPAS learning outcomes between the class using the Picture and Picture model assisted by Wordwall and the class using conventional learning, as indicated by the t-test results with t-count = 13.18 and t-table = 2.01 (t-count > t-table); (2) the Picture and Picture model assisted by Wordwall had a large effect on students’ IPAS learning outcomes, with an effect size value of 1.89; and (3) students responded positively to the Picture and Picture learning model, with a positive response rate of 65%. Based on these findings, the Picture and Picture learning model assisted by Wordwall can be used as an effective alternative learning model and medium.